2003
DOI: 10.1115/1.1760530
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Reduced NOx Emissions in Pilot-Ignited Natural Gas Engines

Abstract: The performance and emissions of a single-cylinder natural gas fueled engine using a pilot ignition strategy have been investigated. Small diesel pilots (2–3% on an energy basis), when used to ignite homogeneous natural gas-air mixtures, are shown to possess the potential for reduced NOx emissions while maintaining good engine performance. The effects of pilot injection timing, intake charge pressure, and charge temperature on engine performance and emissions with natural gas fueling were studied. With appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…However, increasing the naturalgas equivalence ratios w NG at fixed T in and Q inj led to only higher peak heat release rates without affecting the T pPEAK_AVG values significantly. These results are in agreement with experimentally measured trends [18,20] for NO x emissions, which were relatively unaffected as w NG was increased (at fixed Q inj ) to attain engine loads as high as 12 bar BMEP.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, increasing the naturalgas equivalence ratios w NG at fixed T in and Q inj led to only higher peak heat release rates without affecting the T pPEAK_AVG values significantly. These results are in agreement with experimentally measured trends [18,20] for NO x emissions, which were relatively unaffected as w NG was increased (at fixed Q inj ) to attain engine loads as high as 12 bar BMEP.…”
Section: Discussionsupporting
confidence: 81%
“…While the higher T pPEAK_AVG may lead to slightly higher NO x emissions at higher w NG , this increase will probably be modest compared with the influences of T in and Q inj on NO x . This is largely because, as w NG was increased to 0.56, the T pPEAK_AVG value attained was still lower than the critical NO x formation temperature of 2000 K. Consequently, engine-out NO x emissions with ALPING combustion remained very low even when the engine load was increased by increasing w NG , a fact that was demonstrated experimentally in previous studies [18,20].…”
Section: Pilot Fuel Quantity Effectsmentioning
confidence: 49%
See 1 more Smart Citation
“…The amount of NOx resulting from such a method of ignition though very low is limited by the NOx formation resulting from the diesel pilot itself. Krishnan et al [29] have tried using very advanced timing for the diesel pilot in order to reduce the NOx formation. Others have tried to reduce the amount of the diesel pilot as a fraction of the total fuel introduced in to the cylinder with promising results [30].…”
Section: Diesel Pilot Ignitionmentioning
confidence: 99%
“…The 2 Copyright © 2015 by ASME diesel injection timing in [6,7] was fixed. During the studies of pilot-ignited dual fuel combustion, Alla et al [8], Singh et al [2], Krishnan et al [9] and Srinivasan et al [10] found that a change in diesel injection timing had a significant effect on the combustion performance of dual fuel combustion. The combustion performance of dual fuel combustion could also be affected by intake conditions [2,9], exhaust gas recirculation [11], and cetane number of diesel fuel [12].…”
Section: Introductionmentioning
confidence: 99%